Organizational Improvements by Brand Building Strategies in Axia Academy - Tin, Shin Thed; Fadzill, Faudziah Hanim (UUM Press, 2018)
The training industry is a very competitive and an established market. Lots of corporate training company are introduced yearly and even there is exhibition to showcase the upcoming releases. With lots of corporate training companies around the country, some of the company even need to end their operation because of so many factors. Since the market is getting more competitive and changing daily, new comer like Axia Academy Sdn Bhd (AASB) need to find ways to survive. They are facing strong challenges and competitions in the dynamic market. Sales and Marketing Department need to come out with effective plan, Human Resources Department need to recruiting suitable talent and Finance Department need to strengthen cash flow that deeply impact on its daily operation system. Therefore, by using SWOT analysis strategy, AASB has gone through comprehensive exercise to look in- depth for solutions. Strategies involved in market positioning and decision making has been recommended to overcome in Sales and Marketing Department. Human Resources Department has been recommended to leverage on latest technology, while Finance Department to use smart accounting to strengthen company's cash flow. Good service, competitive price and good quality of are some of the minimum requirement needed from consumers. Building brand equity is the major essence to gain customers in a faster track for Axia Academy. This has been a big challenge from timeline, to retain customers confidence and loyalty towards its services.